POTENSI CADANGAN KARBON DAN SERAPAN CO2 ACACIA MANGIUM DI TAMAN KEANEKARAGAMAN HAYATI PT TIRTA INVESTAMA, CISALAK, SUBANG - Sri Utami, Widia; Juliani, Rany; Abidin, Zaenal; Santoso, Sidik; Rahayu, Apriliyanti Dwi; Ankhoviyya, Nida (Jurusan Kehutanan, 2023)
The Biodiversity Park PT Tirta Investama Cisalak Subang Regency has an area of ± 5,800 hectares which has social, economic and environmental benefits. The Biodiversity Park is one of the efforts to support Indonesia's Nationally Determined Contribution target in mitigating climate change by increasing plant land cover, especially tree-level plants. Tree-level plants at a young age can increase carbon stocks in biomass. Younger stands can absorb more carbon than older stands. Climate change can cause natural disasters such as landslides. Landslides that occur in the work area can cause carbon stock loss. Data were collected by census by inventorying diameter at breast height and total height. Data analysis on standing tree volume used a specific gravity of 0.507 and biomass expansion factor of 1.33. Carbon potential research on Acacia mangium to determine the carbon potential of Taman KEHATI which is carried out by census and to determine CO2 absorption. Acacia mangium is an invasive plant that can grow on critical land and marginal land and has fast growth so that it can be used as one of the types for planting activities on post-landslide land. The aboveground carbon biomass research results in units per hectare are 1.690 tons/ha, carbon absorption of 0.794 tons/ha, and CO2 absorption of 2.912 tons/ha.